Sustainable Nature-Based Landscaping and Environmental Conservation: A Case Study of Faculty of Engineering, Imo State University, Owerri - Happiness Ebere Emeribe; Ihuomachuchukwu Ucheoma; Ephraim Uwakwe; Favour Ahamefule; Ephraim Ibe (Darul Yasin Al Sys, 2026)
Although urban landscape studies have largely emphasized large-scale parks and green infrastructure, limited attention has been given to small-scale but high-impact spaces such as building entrances, particularly within educational institutions. This study aims to redesign the entrances of the Agricultural Engineering (AGE) and Civil Engineering (CVE) Departments, Faculty of Engineering, Imo State University, Owerri, using sustainable landscape practices and Nature-Based Solutions (NBS). A site assessment was conducted to develop a sustainable landscape plan that integrates ecological functionality with existing soil conditions, topography, vegetation, biodiversity, and ecosystem services. The redesign incorporated grasses and native plants to enhance site aesthetics, support rainwater absorption, and reduce flooding risk. Clearly defined walkways bordered by kerbs were introduced to guide pedestrian movement while improving functionality and visual quality, and a designated car entrance was created to ensure smooth vehicular access without disrupting the natural layout. The findings show that NBS-based entrance design can enhance aesthetics, functionality, institutional identity, ecological performance, and interdisciplinary relevance across the humanities, engineering, and arts. The study concludes that university entrance spaces can function beyond ornamental purposes by becoming dynamic ecological systems that provide environmental, educational, and psychological benefits. Its contribution lies in demonstrating that the integration of Nature-Based Solutions in institutional landscapes can strengthen climate resilience, improve visual appeal, support Sustainable Development Goals, particularly SDG 11 and SDG 15, and position entrance spaces as critical ecological nodes that shape first impressions, influence microclimatic conditions, and guide future landscape research and design.